Irreversible renal damage from accidental mushroom poisoning. (10th August 2012) - Evans, Nicholas; Hamilton, Alexander; Bello-Villalba, Maria J; Bingham, Coralie
Abstract : Nicholas Evans, author of The Horse Whisperer, tells the story of his journey through acute renal failure to successful transplantation.